Social robot PIO intervention for improving cognitive function and depression in older adults with mild to moderate dementia in day care centers: A randomized controlled trial. - Jun-Seo Lim; Hye-Kyung Oh (PLoS ONE)
The increases in the older population, the prevalence of dementia, and the resulting social costs are burdensome to individuals, families, and the nation. This study examines whether the social robot PIO program intervention is effective for cognitive function and depression for older adults with mild to moderate dementia using two daycare centers in Daegu, Korea. Older adults with mild to moderate dementia and using a daycare center were included in the experimental (n = 33) and control (n = 33) groups. The experimental group participated in the social robot PIO program twice a week, 12 sessions, 50 minutes day for 6 weeks, and the control group received the usual care. From October 2022 through December 2022, a total 66 participants were included. Results showed that the cognitive function of the experimental group increased by 3.9±3.66, from 18.1±4.54 before intervention to 21.9±5.17 after intervention; the control group increased by 0.1±4.13, from 18.2±4.91 before intervention to 18.2± 4.77 after intervention. The difference between the two groups was statistically significant (t = 3.94, p<.001). Depression decreased -0.7±3.48 in the experimental group, from 5.9±4.74 before intervention to 5.2±4.65 after intervention, and decreased by -0.2±3.42, from 6.5±4.69 before intervention to 6.4±4.08 after intervention, in the control group, but the difference between the two groups was not statistically significant (z = -0.59, p =.557). It was confirmed that the social robot PIO program is effective in improving cognitive function in older people with mild to moderate dementia who use daycare centers. Therefore, it is recommended to periodically implement this program for the older adults who use daycare centers to improve cognitive function. The experimental group had lower depression than did those in the control group, but the effect is not statistically significant, so additional research is required. Trial Registration: CRIS (KCT0007936).